ANALISIS PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANASIAL TERHADAP KINERJA PEGAWAI PADA BADAN PUSAT STATISTIK (BPS) PROVINSI NUSA TENGGARA BARAT - isa, isa (Jurnal Magister Manajemen, 2015)
This study aims to investigate the effect of financial and non-financial compensation, either partially or simultaneously, on the employee work performance of Central Bureau of Statistics of West Nusa Tenggara. The study also aims to determine the most dominant variablesinvestigated that affect the employee work performance. The study uses an associative-causal research approach aiming to reveal the relationship between two or more variables. Population of the study consisted of 68 people and they were taken entirely as a respondent. To collect data, a questionnaire instrument was used. Proir to the study, the instrument was tested todetermine its validity and reliability. Further, the study employed multiple linear regression with statistical test of determination (R2), t-test (partial test), F-test (simultaneous test),and individual coefficient of determination (r2 test). Result of the study show that: (1) Financial Compensation had no significant effect on the employee performance but non financial compensation did significantly influence the employee performance. (2) There was a significant effect of the simultaneous Financial Compensation and Nonfinancial Compensation on the Employee Performance. (3) The nonfinancial Compensation had indeed a dominant influence on the employee performance. For future research,it is suggested if the study analyzed the effect of compensation on employee performance, especially in government agencies that have earned remunisasi (Performance Benefit),future researchers not include financial compensation variables and add other variables that can affect the employee work performance such as employee behaviors, leadership style, working conditions, working environment, the complexity of task, and other similar others.From the theory of independent variables studied should be even more so that it can be seen that the dominant variable and the most dominant influence employee performance. Keywords: Employees performances, Financial Compensation, Non Financial Compensation..